Economic Aspects of Tobacco Products’ Contraband - Dimitrov, Dimitar (Research Papers, 2020)
Smuggling of cigarettes has serious economic aspects. It affects tax and excise revenues, increases social spending on health care, government spending for counteraction. Tobacco smuggling and revenues from tobacco smuggling support other criminal activities and act in symbiosis with them. This report addresses the principal effects and influences of smuggling of tobacco products, and in particular their impact in Bulgaria.